PEMANFAATAN LIMBAH SABUT KELAPA SEBAGAI PRODUK UNGGULAN LOKAL - Supriyanto; ningtyas, kurnia rimadhanti; Sarono; Analianasari; Nugraha Agassi, Taufik; Gina Putri, Pridata; M Perdiansyah MH (Politeknik Negeri Lampung, 2022)
Coir is a fairly large part of the coconut fruit, which is 35% of the total weight of the fruit. Coconut coir consists of fibers and cork that connect one fiber to another. Fiber is a valuable part of coir. Each coconut contains 525 grams of fiber (75% of coir), and 175 grams of cork (25% of coir). The classification of fiber based on its origin is that coconut coir fiber itself is a type of natural fiber derived from the coconut plant, namely the fruit. Coconut coir when decomposed will produce coir fiber (cocofibre) and coir powder (cococoir). The purpose of the activity is to improve the understanding and skills of farmers around the Darul Iman Islamic Boarding School in Tanjung Sari Village, Natar District, to utilize coconut coir waste into products that have local competitiveness, namely brooms and doormats. The activities are carried out by learning by doing with the stages of socialization, counseling, direct implementation direct practice, and evaluation.